TECHNIQUE TRANSLATION IS A TYPE OF SPECIAL TRANSLATION - Rakhmonqulova Dilshoda Murodkuziyevna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation   In this article we are talking about the translation of military texts and materials affecting the successful mastery of a foreign language by military personnel. A new requirement for language training specialist means the need to improve the language abilities of students and increase their motivation to learn languages. Some types and ways  of  translations,  typical  properties  of  the  transfer  of  military  materials  are considered. Some studies of the translation of military terms have been studied.